Les manuscrits islandais médiévaux dans les romans islandais contemporains : l’exemple de L’Énigme de Flatey - Quéret-Podesta, Adrien (Romanica Silesiana, 2021)
In the rich history of Icelandic literature, the most famous literary genres are undoubtedly the medieval sagas and the contemporary criminal novels. However, those genres are as not as far from each other as one may think, since masterpieces of Icelandic medieval literature are sometimes summoned by contemporary authors, as is shown in The Flatey Enigma (Icelandic: Flateyjargáta), a criminal novel by Viktor Arnar Ingólfsson which is built around the story and the contents of the Book of Flatey, a famous fourteenth Icelandic manuscript. The present article provides an analysis of the place and function of the manuscripts and the medieval texts it contains: the results obtained show that their main function is to help the development of the plot, although some intertextual references also have a didactic dimension, whereas others provide information about the relations between the characters and the Book of Flatey.